COMPREHENSIVE CONTROL OF PHYSICAL AND COMBAT TRAINING OF CADETS OF THE MINISTRY OF INTERNAL AFFAIRS OF THE ACADEMY - Ibadullayev Balxoja (PEDAGOGS, 2024)
Annotation: Within the framework of professionally applied physical training (PPFP), the selection of funds should not be formally reduced to imitation of professional operations, but should presuppose the predominant performance of actions that allow purposefully mobilizing precisely those professionally important functional properties of the body, motor and related abilities, on which the effectiveness of a particular professional activity significantly depends.